The Pritikin edge : 10 essential ingredients for a long and delicious life - Vogel, Robert A.; Lehr, Paul Tager (New York : Simon & Schuster, 2008)
From a renowned cardiologist and the president of the world-famous Pritikin Longevity Center comes the definitive guide to weight loss and well-being from the longest running, most scientifically documented lifestyle program.
Includes indexes.
Keywords: Low-fat diet; Health; Coronary heart disease -- Diet therapy